Filozofia tożsamości Schellinga. Pierwsze wersje - Piórczyński, Józef (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
The article analyses two first Schelling's works devoted to philosophy of identity: "Darstellung meines Systems der Philosophie" from 1801 and dialogue "Bruno oder über das göttliche und natürliche Prinzip der Dinge" from 1820. In the first one the absolute mind is presented as absolute qualitative identity of object and subject, as absolutely simple and not diverse substance. The form of being of absolute identity is cognition, which realises as infinite constitution of object. Particular things as potencies are quantitative difference between that which is subjective and that which is objective. According to dialogue Bruno, idea as true and eternal reality is unity of what is real and ideal, finite and unfinite. On the other hand, finite things contain their opposite (lack of unity) of their components.